Materials and technologies for the restoration of tower-type objects - S. G. Sheina; D. K.-S. Bataev; M. M. Maloroev; P. D. Bataeva (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to develop a repair and restoration composition of materials and a technology for restoring a tower-type object.Method. The experimental method of destructive and non-destructive quality control of building materials was used in the work; comprehensive instrumental technical inspection of buildings and structures; visual inspection of buildings and structures.Result. A situational review of the object of cultural heritage was carried out. Physical and mechanical tests were carried out in order to select the restoration composition for masonry walls of tower buildings. The results of a visual inspection are presented, on the basis of which a comprehensive assessment of the state of a cultural heritage object is given for carrying out repair, restoration and restoration work at this object. The conclusion of a comprehensive instrumental technical survey on the condition of the object was drawn up. The composition of materials for the repair, restoration and restoration of tower-type cultural heritage sites has been determined.Conclusion. As a result of the technical survey, it was found that the general condition of the facility is emergency. A repair and restoration composition has been developed that, in its properties, is as close as possible to the original, more efficient and contributes to improving the quality of work and the durability of a cultural heritage object.